Leadership styles and job satisfaction :a test on government sector in Selangor - Norshahleha, Ayob. (UNIMAS, 2009)
This study aims to identify and determine the relationship between transactional leadership and transformational leadership with job satisfaction among employees on government sector in Selangor.There are 300 questionnaire had been distributed randomly but only 200questionnaire that can be used. The overall findings showed that the transformational leadership style has a significant relationship with job satisfaction on government sector in Selangor. The result findings of this study might be useful to government sector to create better of environment in organization and help employees to be more productive with their job through more innovative activities in order to achieve the goals of organization.